Physical and technical differences between domestic and foreign soccer players according to playing positions in the China Super League - Gai, Y.; Leicht, A. S.; Lago, C.; Gómez, M.-A. (Research in Sports Medicine, 2019)
Physical demands and technical skills of different playing positions within soccer match-play have been rarely studied in competitions from Asia that have unique restrictions that limit the number of foreign players per team. Therefore, the aims of this study were to identify the technical and physical differences between domestic and foreign soccer players according to playing-positions in the China Super League (CSL); and to classify domestic and foreign players (best/worst) based on their match performance characteristics. Data were provided by Amisco Sports Analysis Services (n = 3468 observations). Discriminant and ANOVA analyses showed important differences between domestic and foreign players in the CSL in terms of physical and technical performance indicators for various playing positions. The unique match performance profiles of domestic and foreign players within the CSL highlighted important features for coaches and managers to improve the recruitment process within a league that implements a restrictive foreign player policy.